Designing of Insufflator for Endoscopic Surgery in Experimental Animals - Motko, A. V.; Dolgopyatenko, A. D.; Chizh, N. A.; Avrunin, O. G.; Sandomirsky, B. P. (Problems of Cryobiology and Cryomedicine, 2016)
Probl Cryobiol Cryomed 2016; 26(2):190.